Karakteristik Denyut Nadi Kerja dan Jumlah Pemakaian Energy pada Tarian Tradisional Bali Memenuhi Kriteria Aktivitas Fisik Erobik Intensitas Ringan - Sedang yang Bermanfaat untuk Mahasiswa Fakultas Kedokteran Universitas Udayana - Adiartha Griadhi, I Putu; Inten Dwi Primayanti, Dewa Ayu (Sport and Fitness Journal; Volume 2, No.2, 2014)
Aerobic physical activity that is carried out by someone with the proper intensity will providehealth benefits. Intensity aerobic activity is recommended moderate intensity, based on thepulse. Traditional dance is one of the AF aerobic. However, no studies have investigated howthe pulse pattern dancer when this traditional dance and how much energy consumption ofthis traditional dance. This study will provide scientific evidence that supports the traditionaldance as one of the aerobic physical activity choices. The study involved eight studentsdaughters to dance three types of traditional Balinese dance are common, namely Tari SekarJagat (TSJ), Tari Cendrawasih (TCN) and Tari Panyembrahma (TPM). Pulse measurementis done by using Telemetry Garmin Forerunner 404 continuously until the end of the dance.Measurement of the amount of energy used during the dance is the online calculation of theworkload on the Garmin website. The results showed that all three types of dance meets thecriteria of mild intensity aerobic physical activity - being. Highest pulse work found in theTCN pulse reaches 78% of maximum, while the TSJ and TPM, respectively 65% and 62%.The third dance training zone and reach steady state for 6 to 8 minutes. Highest energyconsumption found in dance TCN by 40 Calories, and TSJ and TPM, respectively 27 and 21Calories. Thus the three traditional Balinese dance meets the criteria as a mild-intensityaerobic exercise - is that can provide health benefits for dancers.
Keywords: work pulse rate, energy expenditure, traditional dances